CSC264: Introduction to Web and Mobile Application / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
The course introduces the students to web programming. It covers, among others, mark-up language, client-side scripting, and server-side scripting.